1981
DOI: 10.2307/3544439
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Seston Capture by Net-Spinning Caddisflies

Abstract: Six species of net-spinning caddisflies (Trichoptera) coexist in the headwater region of the Tallulah River, a rocky, high-gradient tributary of the Savannah River. These caddisflies feed on the suspended organic matter (seston) captured by their nets. We analyzed these species' nets, microhabitat preferences, and monthly abundances. These data, along with the particle size distributions and monthly abundances of seston, were incorporated into a model of seston capture by these net-spinning caddisflies.The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…Gut content analyses have demonstrated the importance of carnivory and diatom ingestion in many hydropsychid species (Coffman et al, 1971 ;Benke & Wallace, 1980 ;Fuller & Mackay, 1980 ;Ross & Wallace, 1983), suggesting that the low hydropsychid production in headwater streams results from the limited availability of high quality food (Georgian & Wallace, 1981) . In Rose Creek, enrichment by agricultural runoff may contribute to hydropsychid productivity by subsidizing algal growth and production of potential prey species .…”
Section: Production and Turnover Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut content analyses have demonstrated the importance of carnivory and diatom ingestion in many hydropsychid species (Coffman et al, 1971 ;Benke & Wallace, 1980 ;Fuller & Mackay, 1980 ;Ross & Wallace, 1983), suggesting that the low hydropsychid production in headwater streams results from the limited availability of high quality food (Georgian & Wallace, 1981) . In Rose Creek, enrichment by agricultural runoff may contribute to hydropsychid productivity by subsidizing algal growth and production of potential prey species .…”
Section: Production and Turnover Ratesmentioning
confidence: 99%
“…These animals collect and consume drifting material and thus slow the downstream loss of nutrients and energy from the stream system (Wallace et a!., 1977) . Although their impact on total seston quantity may be negligible, filter-feeders can decrease seston quality by removing easily assimilated material, thereby influencing food availability to downstream communities (Maciolek & Tunzi, 1968 ;Carlsson et al, 1977 ;McCullough et a!., 1979 ;Oswood, 1979 ;Benke & Wallace, 1980 ;Georgian & Wallace, 1981 ;Haefner & Wallace, 1981) . Filterfeeder production, defined as tissue elaborated over time (Waters, 1977), represents nutrients and energy Hydrobiologia 112, 3-15 (1984) .…”
Section: Introductionmentioning
confidence: 99%
“…Stream filter feeders exhibit intra-and interspecific aggressiveness in both laboratory and field studies (Edington 1965, Glass and Bovbjerg 1969, Hemphill and Cooper 1983, Hart 1986, Gatley 1988, Hemphill 1988, Hershey and Hiltner 1988, and there exists indirect evidence that interspecific competition for suitable sites for nets may have driven the evolution of net-spinning caddisflies (Georgian and Wallace 1981, Alstad 1986, Thorp et al 1986). Gut analyses (Benke and Wallace 1980) and behavioral studies (Petersen 1985) have shown that the larger hydropsychid larvae feed selectively on high-quality food items such as diatoms and drifting animals, despite the fact that these materials compose only a very small portion of the particulate organic matter (POM) transported by streams (e.g., Parker and Voshell 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Coexistence of species of thegenus Hydropsyche is a common feature in rivers (BOON, 1979;MALAS & WALLACE:, 1977;HILDREW & EDINGTON, 1979; ANDERSEN & KLVB- NES, 1983;HIGLER & TOLKAMP, 1983;GEORGIAN & WALLACE, 1981; HERRANZ 8r GARC~A DF: J A L~N , 1984). I n this basin Hydropsyche bulbifera, Hydropsyche pellucidula and Hydropsyche siltalai coexisted a t the sites which showed higher species richness such as sites 2 and 3 of the main river.…”
Section: Discussionmentioning
confidence: 99%